Tipologi Kontruksi Makna Kata - M. Azizzullah Ilyas (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2020)
The word Taliban has been used by the public and is widely known as the name of the faction of the armed political movement in Afghanistan. However, in the past some time, the term Taliban is often used as a name for a group within the Corruption Eradication Commission (KPK). This raises different meanings and different perceptions. This study aims to analyze how the word Taliban is understood and used in the KPK, how the shape shifts in meaning, and how the construction process patterns. This study uses a descriptive-qualitative approach with data taken from literature and it is enriched with interview and questionnaire data. This study found that the development of meaning was unpredictable but found conclusions in synchronic phenomena when there was a large and open use of words. The common conception and common understanding on the word "Taliban” is doubtful because it can be broadly constructed. The semantic fields used are nouns and adjectives with various meanings. Meaning is constructed from individual perspectives, social and cultural contexts, the it is continued to mutual understanding and natural agreement. Peryoration and amelioration types were the most noticeable patterns of change. However, the positive-positive meaning is also a different pattern found in shifting the meaning of the Taliban in the KPK.